PR excellent creative with integrated event budget calculator (PRECEBC) - Soon Li, Lee (2012)
PR Excellent Creative is a company which is doing public relation in managing variety of event.The PR Excellent Creative is ready to provide their clients the best events and exhibitions with vibrant,dynamic and energizing creative strategy throughout east coast of peninsular Malaysia. This company always needs to competitive with variety of event based management companies in whole of Malaysia.The creativity and innovation of company need to inspire to open new market in anywhere.Because of this problem,they try to promote their company using web.The main objective for doing website is let more their client more understand about the background of company and it will leading them to be giving trust to them.In this proposal project involved of three main users,there are admin,member and external user.